Novel Herbal Gel Formulation of Terminalia chebula Retz., Plant - R. Bhramaramba; K. Hari Prasath; Ch. Amulya (Pharmaceutical Science: New Insights and Developments Vol. 1, 2024)
A novel approach was adopted for developing a herbal gel using Terminalia chebula Retz., a plant revered as the "King of Medicine" in Tibetan traditional medicine. This plant thrives in tropical and subtropical regions of East Asia at altitudes of up to 2000 meters, with optimal growth conditions in areas receiving 100–150 cm of annual rainfall and temperatures ranging between 0–17°C. The plant is a rich source of bioactive compounds, including steroids, flavonoids, tannins, reducing sugars, belleric acid, bellericoside, chebulinic acid, gallic acid, ethyl gallate, punicalagin, terflavin A, terchebin, luteolin, and tannic acid. These constituents contribute to its diverse pharmacological properties, including antibacterial, antifungal, analgesic, anti-inflammatory, wound-healing, and sunburn-soothing effects. Herbal medicines are the oldest form of health care known to mankind. Gel formulations prepared with Carbopol 940, triethanolamine and Propyl Paraben showed good homogeneity, no skin irritation, good stability and anti-inflammatory activity and gel formulations with varying concentrations of T. chebula extract were prepared and assessed. Among the formulations tested, the 5% concentration demonstrated superior performance across all evaluation parameters. This indicates its potential as an effective and alternative option for therapeutic applications and advanced drug delivery systems.